Draft genome sequence of Janthinobacterium lividum strain MTR reveals its mechanism of capnophilic behavior. Issue 1 (December 2015) - Valdes, Natalia; Soto, Paola; Cottet, Luis; Alarcon, Paula; Gonzalez, Alex; Castillo, Antonio; Corsini, Gino; Tello, Mario
Abstract Janthinobacterium lividum is a Gram-negative bacterium able to produce violacein, a pigment with antimicrobial and antitumor properties.Janthinobacterium lividum colonizes the skin of some amphibians and confers protection against fungal pathogens. The mechanisms underlying this association are not well understood. In order to identify the advantages for the bacterium to colonize amphibian skin we sequencedJanthinobacterium lividum strain MTR, a strain isolated from Cajón del Maipo, Chile. The strain has capnophilic behavior, with growth favored by high concentrations (5 %) of carbon dioxide. Its genome is 6, 535, 606 bp in size, with 5, 362 coding sequences and a G + C content of 62.37 %. The presence of genes encoding for products that participate in the carbon fixation pathways (dark CAM pathways), and the entire set of genes encoding for the enzymes of the glyoxylate cycle may explain the capnophilic behavior and allow us to propose that the CO2 secreted by the skin of amphibians is the signal molecule that guides colonization byJanthinobacterium lividum.